Halal food based on maqâshid al-syarî’ah perspective - Wahyudi, Rofiul; Mutmainah, Lu'liyatul; Ali, Maimunah Binti (Universitas Ahmad Dahlan, 2021)
Halal food is essential for the life of a Muslim. Islam is very concerned about the halal aspect to safeguard the benefit of mankind. Halal food from the perspective of maqâshid al-syarî’ah is something that needs to be realized and understood so as not to cause harm. This study aims to explore and analyze the urgency of halal food from the perspective of maqâshid al-syarî’ah. Qualitative methods in the form of content analysis and literature study from secondary data were carried out in this study. Research shows that consuming halal food is very important in maintaining the five essential components in maqâshid al-syarî’ah, namely the maintenance of religion, soul, mind, descent, and property. Muslims must have awareness and understanding regarding every product they consume and producers should ensure the halal supply chain in processing their food products.